PENGARUH CITRA MEREK, HARGA, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE LENOVO DI KOTA DEMAK - Rofiul Nizar, 14.05.51.0120; Setiawan, Mulyo Budi (Students' Journal of Economic and Management, 2018)
This research aims to find out the influence of brand image, price, and product quality toward buying decision of smartphone Lenovo on people at Demak city. The population in this research is the people in Demak who make purchases and use Lenono smartphones. Sampling using Purposive Sampling technique and the questionnaires are distributed to 97 respondent. Data analysis techniques used in this research is validity test, reliability test, normality test, multikoliniarity test, heteroskedastisity test and multiple linier regression. The result of this research showed that brand image and quality of product has significant and positive influence toward buying decision. Nevertheless the price did not significantly influence with positive direction to the buying decision. Keywords: Brand Image, Price, Quality of Product, Buying Decision